Kompensasi dan Benefit dalam Meningkatkan Kinerja Sumber Daya Manusia - Hermawan, Eric; Gusmao, Cristino; Amaral, Leonardo Bele Bau; Sarmento, Angela Laura Sofia; Shofwani, Siti Aniqoh (Jurnal EMT KITA, 2025)
The presence of Entrepreneurship Education in higher education remains a vital pathway to develop young, educated entrepreneurs. This research aims to examine the role of Entrepreneurship Education in enhancing students' entrepreneurial self-efficacy, which in turn may increase their interest in pursuing entrepreneurship. To achieve this objective, a quantitative study was conducted using a survey method. A total of 116 students from several private universities in the Jakarta area participated by completing a questionnaire that was designed using Google Forms and distributed via WhatsApp. The data were analyzed using Structural Equation Modeling with the Partial Least Squares method. The findings of the study indicated that Entrepreneurship Education significantly boosts students' entrepreneurial self-efficacy, leading to a heightened interest in entrepreneurship. The moderating effect of Entrepreneurship Education on Entrepreneurial Self-Efficacy was classified as very high (f² = 0.102), as this value exceeds the threshold suggested by Kenny (2018) in Hair et al. (2022), which indicates that an f² value of 0.025 is considered high.
Keywords: Entrepreneurial Interest; Entrepreneurial Self-Efficacy; Entrepreneurship Education; Moderation